Carbon Nanotubes (CNTs) for Prolonging the Life of Micropunch - Guo, Kelvii Wei; Tam, Hon Yuen (Journal of Coating Science and Technology, 2015)
Carbon nanotubes (CNTs) coated on the WC/Co micropunch with diameter in 150 μm for prolonging the life of micropunch was investigated. Carbon nanotubes were synthesized by homemade method. With scanning electron microscopy (SEM) and transmission electron microscopy (TEM), the morphology and structure of CNTs had been expressed. After the punching test with Ti as substrate, the effect of CNTs for prolonging the life of micropunch on the wear loss and the surface morphology of micropunch had been studied by confocal laser, SEM, digital balance etc. Results show the wear of CNTs coated micropunch decreases obviously. Even in the severe wear period the wear loss is less than that of non-CNTs coated micropunch. Compared with the micropunch without CNTs coating, the promising results are due to the formation of a transfer film at the contact region by rubbing of the CNT forest, CNTs produced adheres to the micropunch surface avoiding direct contact during the punching period and providing lubricant properties to the interface by virtue of their graphitic nature. Also, the relevant mechanism was illustrated primarily.